BIHON TYPE NOODLES FROM HEAT MOISTURE TREATED STARCH OF FOUR VARIETIES OF SWEET POTATO [Mi Tipe Bihun dari Pati Heat Moisture Treatment dari Empat Varietas Ubi Jalar] - Vera Apryana Lase; Elisa Julianti; Linda Masniary Lubis (Jurnal Teknologi dan Industri Pangan, 2013)
Sweet potato starch has limited uses in food industry, but modification of its properties may make it more suitable for use especially for starch based food such as bihon type noodle. The objective of this research was to study the effect of heat moisture treated starch from 4 varieties of sweet potato on the quality of its bihon type noodle. Four different varieties of sweet potato i.e. white, yellow, orange and purple tuber were treated with heat moisture treatment (HMT). The HMT was performed by exposing the starch to high temperature (110°C for 3 hours) at a moisture content of 25%. The HMT modified sweet potato starch was then processed into bihon type noodle. As a control, a commercial bihon type noodle made from rice starch was used. Parameters evaluated were the modified starch and bihon properties. The results showed that the modification of starch with HMT could increase the peak viscosity, setback viscosity, final viscosity and gelatinization temperature but lower the value of the breakdown viscosity. The best bihon from the four varieties of sweet potatoes was that made from white sweet potato starch because it has low cooking losses, low fat, but has high color/brightness and is preferred by panelist.